Pengembangan Standarisasi Pondok Pesantren - Sidiq, Umar (Nadwa, 2013)
Pesantren as a forerunner to the original Indonesian educational institution just legally recognized in 2003 through the National Education Law No. 20/ 2003. The pesantren educations that were initially oriented only on deepen-ing religious knowledge have begun to include general subjects. The inclu-sion of these subjects is expected to expand the horizons of studentsâ thought in which they will also take the national examination held by the govern-ment. The informal education outcomes are appreciated to be equivalent to formal education after passing the assessment of equivalency process con-ducted by agencies appointed by the government or local authorities by ref-erence to national education standards. The pesantren has a special place and position in the national education system. Therefore, the pesantren should always make improvements and increase its education quality.